Essays on remittances and climate variability in Burkina Faso - (:unkn) unknown (My University, 2017)
Environmental and climate issues constitute a predominant and much up to date topic in international discussions. It is broadly recognized that developing countries are the most vulnerable when it comes to climate issues, albeit, they are the least responsible. Finding ways for households’ of these countries to cope with the harmful effects of climate goes through the necessity to identify mechanisms that can help, such as migration and remittances. The latter have been found in the scientific literature to be a hedge against several shocks such as natural disasters, conflicts, and economic shocks.This research thesis explores the theme of remittances, and climate variability in developing countries, by focusing on a sub-Saharan African country, Burkina Faso. Compared to its neighbouring countries, Burkina Faso has not been subject to much research in the migration and remittances. The country however has a vast migration history that is worth studying. Climate issues are also rampant, and very important, as the country is practising subsistence agriculture. The findings of this dissertation show that remittances have a positive impact on households’ ability to cope with the negative effects of climate issues. Yet these important sources of inflows for developing countries might have some limitations. The first chapter assesses the impact of remittances and climate variability on the food security of households in Burkina Faso. We build a food security index using principal component analysis that encompasses the accessibility and utilization dimensions of the concept. We also compute an inter-annual rainfall index and the latter is found to have a negative impact on food security. After controlling for potential endogeneity issues using distance variables and migrant characteristics as instruments, remittances are found to enhance food security. Results are robust to alternative measures of food security and alternative calculations of rainfall
Keywords: African Research